Perakanthus longipetalus (Rubiaceae), a new combination, and the first record of the genus outside Peninsular Malaysia - Neo, Louise; Mahyuni, Ridha; Wong, K.m. (Phytotaxa, 2020)
Canthium longipetalum Y.H.Tan & S.S.Zhou in Yang et al. (2019: 197) is a species of Rubiaceae recently described from northern Myanmar. This species was identified as belonging to the Vanguerieae tribe, and was placed provisionally in the genus Canthium Lamarck (1783: 602) based on morphological characters including the presence of axillary inflorescences, valvate corolla aestivation, two-locular ovaries, and a two-lobed stigma (Yang et al. 2019). However, the suite of characters cited by the authors to support the placement of their species in Canthium define an overly broad and now-superseded concept of the genus.